Overview of quadrivalent immunization in female adolescents against Human Papillomavirus over four years: a cross-region analysis in Brazil (Research, Society and Development, 2022)
Introduction: Human Papillomavirus is one of the major etiologies of sexually transmitted infections and oncogenic diseases in the world, in which it has low and high oncogenic risk viral serotypes (HPV-6, -11, -16 and -18). Many vaccines were developed to contain the spread of infection, among them, the quadrivalent, which provides protection to these viral serotypes. However, vaccination coverage of the immunizer in Brazil is unsatisfactory in different regions of the country, especially in the female adolescent group. Objective: To describe the panorama of female quadrivalent vaccination among Brazilian regions over four years. Methodology: Data were obtained from the public database TABNET - Immunizations, considering: all regions, period from 2016 to 2019, quadrivalent immunizer HPV-female-1st/2nd-doses and age from 10 to 15 years. Data were organized in an Excel spreadsheet and analyzed in RStudio software, in which all the graphic language was produced. Results: It was observed that the number of applications increased in the first biennium of the analysis, but significantly reduced in the second, in addition to the fact that the vaccine scenario of the first dose does not follow the second, directly reflecting the vaccine coverage of the immunizer in the country. Conclusion: the research graphically demonstrated the female quadrivalent vaccine scenario, showing that it is unsatisfactory, since recent studies also highlight the existing gaps in vaccine coverage, in addition to citing the regional heterogeneity regarding the vaccination reality of each location in the Brazil.